The impact of it governance on audit outcomes and footnote readability for public companies in Indonesia - Utama, Indah Wulan; Anridho, Nadia (Jurnal Akuntansi dan Auditing Indonesia, 2024)
This study explores the relationship between IT governance and audit outcomes, including audit costs, quality, report lag, opinions, and the readability of financial statement footnotes in Indonesian public companies. Utilizing regression analysis, the research finds that while IT governance does not significantly affect audit costs, report lag, or opinions, it positively influences audit quality. Contrary to expectations, higher IT capabilities do not lead to increased audit costs but reduce them by lowering audit efforts. Furthermore, IT governance does not notably impact footnote readability, potentially due to information overload in annual reports. These findings shed light on the importance of IT governance in shaping audit quality and provide valuable insights for stakeholders in Indonesian public companies. Further research is encouraged to explore these relationships in different contexts and industries.